A Chronicle of the Bilbao Group from Inside (1996-2014) - Frias Conde, Xavier (Madrygal. Revista de Estudios Gallegos, 2015)
Since 1996, most of the literary production in Galician was carried out by the so-called Grupo Bilbao, a group of writers living in the capital city of Spain, whose main literary language is Galician. There are dozens of questions arising around them, such as identity, exotopia, bilingualism, etc. This paper attempts to give an answer to all these questions from inside the group’s intra-history by following the main hits of its history throughout the last 18 years.
Keywords: Grupo Bilbao; Galician language literature; exotopia; Madrid; identity; O Roibén